A standard of oral hormone replacement therapy in women after menopause – 1 mg of 17β-estradiol plus dydrogesterone? - Pertyński, Tomasz; Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2005)
Low-doses of natural estrogen – such as 17β-estradiol – plus progestin with low, or zero, androgenic, gluco- or mineralocorticoid properties (dydrogesterone) applied in women after menopause allow to reduce some of the typical HRT side effects – breast and endometrial cancers, abnormal uterine bleedings, or cardiovascular illnesses (atherosclerosis, arterial hypertension, venous thrombosis). Being an effective therapy of menopausal complaints and diseases, e.g. osteoporosis, it could be in the near future a standard of oral HRT.